2011
DOI: 10.1038/cgt.2011.84
|View full text |Cite
|
Sign up to set email alerts
|

A novel conditionally replicating adenoviral vector with dual expression of IL-24 and arresten inserted in E1 and the region between E4 and fiber for improved melanoma therapy

Abstract: Although the combination of gene therapy and virotherapy for cancer therapy has obtained some encouraging results in vitro and in vivo over the past few years, some improvements of the vectors are still urgently needed to enhance their therapeutic effects for cancers. In order to maximize the anti-cancer activities of conditionally replicating adenoviral vectors (CRAd) vector, we for the first time generated a novel CRAd vector by inserting an expression cassette between E4 and the fiber using homologous recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A couple of studies have also shown that a CRAd carrying IL-24 helped in inducing apoptosis of melanoma cells following radiotherapy (Chai et al , 2012; Jiang et al , 2012). Thus, the possibility of acting on human melanoma tumors with an oncolytic virus that can target both the stromal and the malignant compartment, respond to melanoma microenvironment, and whose infectivity can be tailored according to cell surface expression of viral receptors can be of significant importance for melanoma therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of studies have also shown that a CRAd carrying IL-24 helped in inducing apoptosis of melanoma cells following radiotherapy (Chai et al , 2012; Jiang et al , 2012). Thus, the possibility of acting on human melanoma tumors with an oncolytic virus that can target both the stromal and the malignant compartment, respond to melanoma microenvironment, and whose infectivity can be tailored according to cell surface expression of viral receptors can be of significant importance for melanoma therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviruses have several advantages over some other viral vectors such as retroviruses and adeno-associated virus. Adenovirus vectors can infect a variety of cell types, including non-dividing as well as dividing cells, and can be prepared readily in large quantities in tissue culture (Vetrini and Ng, 2010;Chai et al, 2012) 1.4.1.5 Adenovirus-based vaccines against infectious pathogens Another promising application for adenoviruses is their use as vaccine vectors (Gaydos and Gaydos, 1995). As already mentioned, live, oral, enteric-coated, adenovirus serotypes 4 and 7 vaccines were safely used for years in military training camps to prevent epidemics of acute adenoviral respiratory disease.…”
Section: The Use Of Adenovirus Vectors For Gene Therapymentioning
confidence: 99%
“…Early versions of dualexpression vectors carried two versions of the same cassette within E1 that differed in the transgene but contained the identical (Zinn et al, 2002) or different (Liu et al, 2012) regulatory elements. Others used bidirectional promoters to control up-and downstream transgenes placed into E1 (Chai et al, 2011) or two expression cassettes with different promoters placed in tandem into E1 (Irie et al, 2005). Others, similar to our approach, inserted one transgene under the control of a CMV promoter into E1 and a second transgene under the control of the RSV promoter into E3 with both expression cassettes in the same orientation (Niu et al, 2006).…”
Section: Dual-expression Adenoviral Vectorsmentioning
confidence: 99%